2021
DOI: 10.1101/2021.06.29.450427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prefrontal cortical connectivity mediates locus coeruleus noradrenergic regulation of inhibitory control in older adults

Abstract: Response inhibition is a core executive function enabling adaptive behaviour in dynamic environments. Human and animal models indicate that inhibitory control and control networks are modulated by noradrenaline, arising from the locus coeruleus. The integrity (i.e., cellular density) of the locus coeruleus noradrenergic system can be estimated from magnetization transfer sensitive magnetic resonance imaging, in view of neuromelanin present in noradrenergic neurons of older adults. Noradrenergic psychopharmacol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…However, this relationship may change with age and disease. Previous studies have shown that maintaining functional connectivity profile is increasingly relevant for older adults to maintain cognitive functions across different cognitive domains (Bethlehem et al, 2020;Bruffaerts et al, 2019;Guardia et al, 2022;Tibon et al, 2021;Tomassini et al, 2022;Tsvetanov et al, 2016;Tsvetanov et al, 2018). Given the ageand cognition-related correspondence between functional connectivity and structural connectivity, we hypothesized that the increased reliance on functional connectivity for cognition in ageing is dependent on structural connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this relationship may change with age and disease. Previous studies have shown that maintaining functional connectivity profile is increasingly relevant for older adults to maintain cognitive functions across different cognitive domains (Bethlehem et al, 2020;Bruffaerts et al, 2019;Guardia et al, 2022;Tibon et al, 2021;Tomassini et al, 2022;Tsvetanov et al, 2016;Tsvetanov et al, 2018). Given the ageand cognition-related correspondence between functional connectivity and structural connectivity, we hypothesized that the increased reliance on functional connectivity for cognition in ageing is dependent on structural connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…We have proposed that the maintenance of cognitive function with advancing age is increasingly dependent on the integrity of functional brain networks (Tsvetanov et al, 2016). This proposal replicates across cognitive states (Tomassini et al, 2022;Tsvetanov et al, 2018), neuroimaging modalities (Tibon et al, 2021), analytical approaches (Bethlehem et al, 2020;Linda Geerligs & Tsvetanov, 2017;Guardia et al, 2022) and in individuals with genetically increased risk of dementia (Chan et al, 2021;Passamonti et al, 2019;Rittman et al, 2019;Tsvetanov, Gazzina, et al, 2021). However, the increased reliance on functional integrity for maintaining cognitive functions in later life is poorly understood.…”
Section: Introductionmentioning
confidence: 91%
“…Human imaging studies have shown that the elevation of extracellular noradrenaline levels (via intake of selective noradrenaline reuptake inhibitors or genetic variation of a noradrenaline transporter gene) can enhance stopping-related right IFG activity ( Chamberlain et al, 2009 , Whelan et al, 2012 , Ye et al, 2015 ). Population-based, cohort studies have reported a relationship between LC integrity and noradrenergic-dependent functions (including response inhibition) ( Liu et al, 2020 , Tomassini et al, 2022 ). Therefore, we propose that the LC-noradrenergic system modulates the right IFG-STN pathway during stopping.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid intelligence represents flexible problem-solving ability, encompassing working memory and executive functions, and typically declines steadily from early adulthood (Manard et al, 2014; de Mooij et al, 2018; Shafto et al, 2020). Though they are positively correlated across individuals, the difference between crystallized and fluid intelligence – the “discrepancy” – is a sensitive measure of within-subject decline arising from brain injury, degeneration and ageing (Dierckx et al, 2008; Harrington et al, 2018; McCarthy et al, 2005; McDonough et al, 2016; McDonough and Popp, 2020; O’Carrol and Gilleard, 1986; O’Shea et al, 2018; Rabbit, 1993; Tomassini et al, 2021). A higher discrepancy score, when subtracting normalised fluid intelligence from normalised crystallized intelligence, indicates greater cognitive decline (McDonough et al, 2016).…”
Section: Introductionmentioning
confidence: 99%